2014
DOI: 10.3892/mmr.2014.2268
|View full text |Cite|
|
Sign up to set email alerts
|

Talen-mediated girdin knockout downregulates cell proliferation, migration and invasion in human esophageal carcinoma ECA109 cells

Abstract: Girdin is an actin-binding Akt substrate that is involved in the regulation of cell migration. Accumulating evidence has revealed that girdin has regulatory effects on invasion and metastasis in several types of cancer. However, the role of girdin in esophageal squamous cell carcinomas (ESCCs) is yet to be investigated. In the present study, tissue microarray data revealed that among 95 cases of ESCC, 27 cases (28.7%) exhibited a low expression of girdin, while 67 cases (71.3%) had an enhanced expression of gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Consistent with these findings, Natsume et al ( 16 ) reported that genetic girdin knockout promoted glioma stem cell differentiation, but inhibited cell motility, invasion, metastasis and proliferation in vivo . Cao et al ( 17 ) demonstrated that girdin knockout reduced esophageal cancer cell proliferation, migration and invasion, which was also similar to the findings of the present study. Girdin deprivation has also been observed to inhibit vascular smooth muscle cell (VSMC) proliferation and to affect actin cytoskeletal rearrangement, resulting the in impaired migration of VSMCs and altered neointimal formation following vascular injury ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with these findings, Natsume et al ( 16 ) reported that genetic girdin knockout promoted glioma stem cell differentiation, but inhibited cell motility, invasion, metastasis and proliferation in vivo . Cao et al ( 17 ) demonstrated that girdin knockout reduced esophageal cancer cell proliferation, migration and invasion, which was also similar to the findings of the present study. Girdin deprivation has also been observed to inhibit vascular smooth muscle cell (VSMC) proliferation and to affect actin cytoskeletal rearrangement, resulting the in impaired migration of VSMCs and altered neointimal formation following vascular injury ( 10 ).…”
Section: Discussionsupporting
confidence: 92%
“…The current study also has implications for our understanding of the role of Girdin as an oncogene in cancer cells, as Girdin knockdown impaired pancreatic cancer cell proliferation and induced apoptosis. Consistent with these findings, scientists have suggested that Girdin knockout inhibits cell proliferation ( 20 ). Girdin has also been shown to directly interact with Par-3, a cell polarity protein, to regulate cell polarity during cell migration ( 21 ).…”
Section: Discussionmentioning
confidence: 73%
“…When the cells reached 80% confluence, Lipofectamin2000 (Invitrogen) was used to transfect miR-101 mimics, miR-101 inhibitor and miRNA NC mimics into HepG2 cells according to the instructions, respectively. According to the method reported by literatures, plasmids were transfected into HepG2 cells in order to perform the knockout of the Girdin gene ( Cao et al, 2014 ). 48h after transfection, the fluorescence microscopy and the qRT-PCR were used to detect whether the cell cloning process was successful.…”
Section: Methodsmentioning
confidence: 99%